AICCRA under Additional Financing: Zambia National Consultation Presentation - Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The purpose of the presentation was to update and inform stakeholders about the AICCRA program; inform AICCRA Zambia partners and stakeholders about the continuation of financing and the rational for AICCRA’s AF, including the new orientations and increased ambitions; and to collect inputs and feedback from stakeholders to consolidate into AICCRA’s AF proposal.